2015
DOI: 10.1088/1748-9326/10/1/014003
|View full text |Cite
|
Sign up to set email alerts
|

Increased dry season water yield in burned watersheds in Southern California

Abstract: The current work evaluates the effects of the 2003 Old Fire on semi-arid systems in the San Bernardino Mountains, California. Pre-and post-fire daily streamflow are used to analyze flow regimes in two burned watersheds. The average pre-fire runoff ratios in Devil Canyon and City Creek are 0.14 and 0.26, respectively, and both increase to 0.34 post-fire. Annual flow duration curves are developed for each watershed and the low flow is characterized by a 90% exceedance probability threshold. Post-fire low flow is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 35 publications
2
62
1
Order By: Relevance
“…To reduce calculation bias due to zero flow days commonly found in ephemeral stream systems, zero flow days were eliminated from exceedance value calculations. High flows were defined similarly, with a 10 % exceedance threshold used to isolate larger volume flows (Kinoshita and Hogue, 2015). Changes in low flows and high flows were calculated as the post-fire percent change from the average of 10 water years pre-fire.…”
Section: Response Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce calculation bias due to zero flow days commonly found in ephemeral stream systems, zero flow days were eliminated from exceedance value calculations. High flows were defined similarly, with a 10 % exceedance threshold used to isolate larger volume flows (Kinoshita and Hogue, 2015). Changes in low flows and high flows were calculated as the post-fire percent change from the average of 10 water years pre-fire.…”
Section: Response Variablesmentioning
confidence: 99%
“…For example, studies in rangeland regions of the US found moderate increases in flow, infiltration, and erosion rates after major wildfires, with trends continuing for as long as 15 years (Emmerich and Cox, 1994;Pierson et al, 2009;Hester et al, 1997;Kinoshita and Hogue, 2015). Fires in chaparral environments, such as in southern California, exhibited increased flows of up to as much as 2 orders of magnitude, with much of this occurring in the dry season (Coombs and Melack, 2013;Hogue, 2011, 2015;Loáiciga et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Kinoshita and Hogue () observed a significant increase in low flows, mostly during interstorm periods, during the first 10 years following another nearby wildfire. Low flows (90% exceedance probability) increased from an order 10‐3 m 3 /s to 10‐1 m 3 /s, or 118% in the 51‐km 2 City Creek watersheds and 1,090% in the 14‐km 2 Devil Creek watershed.…”
Section: Effects On Streamflow By Climate Regionmentioning
confidence: 99%
“…An emerging perspective is that short-term (approx. 10 years) increases in water yield, usually in the form of stream base flow, could be used to augment water supplies [32].…”
Section: Introductionmentioning
confidence: 99%